On predicting wind power series by using BEA modified neural networks-based approach - Rodriguez Rivero, Cristian (2017)
Fil: Rodriguez Rivero, Cristian. Universidad Nacional de Córdoba. Departamento de ingeniería electrónica; Argentina.